METODE DAKWAH DALAM PENGAJARAN NABI PERSPEKTIF HADIS - Adi Abdullah MUSLIM (Jurnal Al-Hikmah: Jurnal Dakwah, 2019)
This article was inspired by the book of al-Rasul al-Mu'allim by ‘Abd al-Fattah Abu Ghuddah. He mentioned that there were about forty classifications of the Prophet's teaching methods as outlined in the form of hadith. The books are written are characterized by forms of educational values. However, in essence the method of education taught by the Prophet was also the way the Prophet conveyed his preaching to his companions. The time of the Prophet who had not yet known communication theories to convey God's messages, gave the results of the formation of strong characters in sahabat Nabi. So what is discussed in this article is about the method of Prophet's preaching in teaching sahabat Nabi the hadith perspective so as to form theories in da'wah communication and education. [Artikel ini terinspirasi dari kitab al-Rasul al-Mu’allim karya ‘Abd al-Fattah Abu Ghuddah. Ia menyebutkan bahwa ada sekitar empat puluh klasifikasi metode pengajaran Nabi yang dituangkan dalam bentuk hadis. Buku yang dituliskan banyak diwarnai dengan bentuk nilai-nilai pendidikan. Namun, pada hakikatnya metode pendidikan yang diajarkan Nabi juga merupakan cara Nabi menyampaikan dakwahnya kepada para sahabat. Di zaman Nabi yang belum dikenal teori-teori komunikasi untuk menyampaikan pesan-pesan Tuhan, memberikan warna dan hasil pembentukan karakter kuat pada diri sahabat. Maka yang dibahas dalam artikel ini mengenai metode dakwah Nabi dalam mengajarkan kepada sahabat perspektif hadis sehingga membentuk teori dalam komunikasi dakwah dan pendidikan]. Kata kunci: metode, nabi, pengajaran, karakter, sahabat